Children's and carers' perspectives of a therapeutic intervention for children affected by sexual abuse. Issue 2 (2nd November 2016) - Jessiman, Patricia; Hackett, Simon; Carpenter, John
Abstract: This paper presents the findings of a qualitative study with children affected by sexual abuse who had recently completed a therapeutic intervention ( N  = 12) and their carers ( N  = 17). Four themes emerged from the thematic analysis that influenced participants' satisfaction with the service: the attribution of the child's recovery to the therapeutic support received; the therapeutic relationship between the child and practitioner; children's recollection of important aspects of the intervention and the relationship between the carer and the child's practitioner. The findings indicate that the process elements of therapeutic support, including the development of strong relationships and allowing children choice and control, are as important as the content.